Pengungkapan Konflik Keluarga di Media Sosial dalam Perspektif Hukum Islam: Menerapkan Prinsip Islah sebagai Solusi Resolusi Konflik - Novita, Dwi; Sar’an, Mohamad; Ahmad Ridwansah, Asep; Suharyono, Suharyono; Ardiansyah, Hamdan (Institut Agama Islam Negeri Curup, 2025)
This study examines the phenomenon of disclosure of family conflicts on social media from the perspective of Islamic law, with particular emphasis on the social and psychological effects and violations of sharia values. Qualitative research methods were used through the analysis of the texts of the Qur'an, Hadith, and Islamic legal literature, as well as case studies of viral conflicts on Instagram, Facebook, TikTok, and Twitter. The results showed that this practice contradicts the principles of ghibah (gossip), namimah (divisive gossip), and ifk (false accusations). These principles violate family privacy and the honor of al-'irdh as part of maqashid syaria. The spread of conflict in the digital public sphere causes greater problems, emotional distress, social stigma, and the separation of family relationships, as seen in viral inheritance, polygamy, and intergenerational conflicts. Solutions offered by Islamic law include the concept of islah, or reconciliation, which emphasizes digital ethics education, mediation by neutral parties, and closed conflict resolution. First, deliberation with good intentions, second, the application of the principle of forgiveness (al-'afw), third, raising awareness about the long-term impact of conflict exposure, and fourth, setting boundaries of privacy on social media. This study found that to maintain family harmony in the digital age, sharia-based ethics education and the principle of islah must be combined. The academic results enhance Islamic legal research on social media dynamics. On the other hand, the practical consequences offer guidelines for practitioners and families to resolve conflicts in a way that is in accordance with Islamic values. Strengthening digital literacy based on prudence and optimizing community-based mediation are two main recommendations.